2020
DOI: 10.1002/jimd.12242
|View full text |Cite
|
Sign up to set email alerts
|

Cln1‐mutations suppress Rab7‐RILP interaction and impair autophagy contributing to neuropathology in a mouse model of infantile neuronal ceroid lipofuscinosis

Abstract: Infantile neuronal ceroid lipofuscinosis (INCL) is a devastating neurodegenerative lysosomal storage disease (LSD) caused by inactivating mutations in the CLN1 gene. CLN1 encodes palmitoyl‐protein thioesterase‐1 (PPT1), a lysosomal enzyme that catalyzes the deacylation of S‐palmitoylated proteins to facilitate their degradation and clearance by lysosomal hydrolases. Despite the discovery more than two decades ago that CLN1 mutations causing PPT1‐deficiency underlies INCL, the precise molecular mechanism(s) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 60 publications
(178 reference statements)
2
18
0
Order By: Relevance
“…Accordingly, CLN8 may impact vesicular traffic in different ways: (1) by direct interaction with proteins associated with vesicular transport (Passantino et al., 2013); (2) by modulating the transport of soluble lysosomal proteins that affect lysosomal biogenesis (di Ronza et al., 2018; Bajaj et al., 2020). For example, palmitoyl protein thiosterase 1 (a lysosomal protein transported by the EGRESS complex; di Ronza et al., 2018; Bajaj et al., 2020) is necessary for the proper location of Rab7a and Rab7a/RILP interaction, proteins involved in the regulation of late endosome/lysosome movement (Sarkar et al., 2020); and (3) by modulating lipid biosynthesis and distribution within cells (Hermansson et al., 2005; Rusyn et al., 2008; Kuronen et al., 2012). Dysregulation of any of these processes can lead to incorrect distribution and recycling of proteins and, ultimately, alterations in vesicular traffic.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, CLN8 may impact vesicular traffic in different ways: (1) by direct interaction with proteins associated with vesicular transport (Passantino et al., 2013); (2) by modulating the transport of soluble lysosomal proteins that affect lysosomal biogenesis (di Ronza et al., 2018; Bajaj et al., 2020). For example, palmitoyl protein thiosterase 1 (a lysosomal protein transported by the EGRESS complex; di Ronza et al., 2018; Bajaj et al., 2020) is necessary for the proper location of Rab7a and Rab7a/RILP interaction, proteins involved in the regulation of late endosome/lysosome movement (Sarkar et al., 2020); and (3) by modulating lipid biosynthesis and distribution within cells (Hermansson et al., 2005; Rusyn et al., 2008; Kuronen et al., 2012). Dysregulation of any of these processes can lead to incorrect distribution and recycling of proteins and, ultimately, alterations in vesicular traffic.…”
Section: Discussionmentioning
confidence: 99%
“…As PE is a key lipid in autophagosome formation, Psd knockdown causes reduced levels of the LC3-PE conjugate ( Midorikawa et al, 2010 ). In a Ppt1 -deficient mouse model, LC3-II levels and autophagosome formation are increased, resulting in an increase in the numbers of autophagosomes ( Sarkar et al, 2020 ; Yun et al, 2020 ). In another study, LC3-II lipidation experiments showed lysosomal inhibition and a decrease in autophagosome accumulation in PPT1 -deficient human cells treated with autophagy inhibitors (e.g., chloroquine (CQ) or a chloroquine-derived molecule DC661), indicating that loss of PPT1 inhibits autophagy ( Rebecca et al, 2019 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%
“…In another study, LC3-II lipidation experiments showed lysosomal inhibition and a decrease in autophagosome accumulation in PPT1 -deficient human cells treated with autophagy inhibitors (e.g., chloroquine (CQ) or a chloroquine-derived molecule DC661), indicating that loss of PPT1 inhibits autophagy ( Rebecca et al, 2019 ). In patient-derived PPT1 -deficient fibroblasts, studies revealed that LC3-II levels did not differ with inhibition of lysosomal acidification in PPT1 -deficient cells but increased in fibroblasts derived from CLN1 disease patients, suggesting that autophagic vesicle turnover independent of lysosomal acidification is reduced ( Sarkar et al, 2020 ). Patient-derived PPT1 -deficient fibroblasts also display decreased LC3 colocalization with both LAMP1 and LAMP2, suggesting altered autophagosomal-lysosomal fusion ( Figure 3 ) ( Sarkar et al, 2020 ).…”
Section: The Roles Of Cln Genes and Proteins In Au...mentioning
confidence: 99%
See 1 more Smart Citation
“…It is an open question as to whether and how parkin regulates these contacts. Interestingly, CLN1 mutations, which cause a form of neuronal ceroid lipofuscinosis similar to CLN8, also suppress Rab7-RILP interaction, leading to impaired autophagy (Sarkar et al 2020).…”
Section: Contribution Of Dysfunctional Interorganelle Communication To Aging and Neurodegenerationmentioning
confidence: 99%